Finite Element Analysis on Nanomechanical Detection of Small Particles: Toward Virus Detection - Imamura, Gaku; Shiba, Kota; Yoshikawa, Genki (Frontiers in Microbiology, 2016)
Detection of small particles, including viruses and particulate matter (PM), has been attracting much attention in light of increasing need for environmental monitoring. Owing to their high versatility, a nanomechanical sensor is one of the most promising sensors which can be adapted to various monitoring systems. In this study, we present an optimization strategy to efficiently detect small particles with nanomechanical sensors. Adsorption of particles on the receptor layer of nanomechanical sensors and the resultant signal are analysed using finite element analysis (FEA). We investigate the effect of structural parameters (e.g. adsorption position and embedded depth of a particle and thickness of the receptor layer) and elastic properties of the receptor layer (e.g. Young’s modulus and Poisson’s ratio) on the sensitivity. It is found that a membrane-type surface stress sensors (MSS) has the potential for robust detection of small particles.